EFFECT OF DILTIAZEM ON RENAL-FUNCTION IN PATIENTS WITH LIVER-CIRRHOSIS - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 1991)
Calcium channel blockers have strong vasodilator, natriuretic and diuretic actions in normal and hypertensive subjects. The aim of this study was to evaluate the effect of diltiazem on renal function, renin-angiotensin-aldosterone axis (RAA) and atrial natriuretic factor (ANF) in paitents with liver cirrhosis. Seven patients (3 females and 4 males) with a mean age of 56.3 +/- 11.1 years (36-68) entered the trial. All of the patients had HBV (6 cases) or HCV (1 case) related Child A (3 cases) or Child B (4 cases) liver cirrhosis proven by liver biopsy. Patients were given placebo for 15 days followed by p.o. diltiazem 30 mg t.i.d. for 15 days. Urinary volume, natriuresis, creatinine clearance, plasma renin activity (PRA), ANF and aldosterone (ALD) levels were determined after the washout period and during the first and second weeks of drug treatment. Urinary volume increased by 25-170% in 5 cases but this difference did not reach statistical significance. Slight increases in natriuresis occured in some cases on the 3rd day of the trial but the overall results were not statistically significant (191.50 +/- 26.85 vs 204.07 +/- 39.83 mmol/l). Diltiazem induced no significant changes in PRA, ALD and ANF levels or creatinine clearance during the first or second weeks of the trial. There was a significant drop in the pulse rate on the first or second weeks of the treatment (p < 0.01 and p < 0.05, respectively). No significant changes were noted on mean arterial pressure (MAP). In conclusion, diltiazem at doses of 30 mg t.i.d. does not seem to exert a significant effect on diuresis, natriuresis, the RAA axis or ANF in patients with liver cirrhosis.
Keywords: CALCIUM ANTAGONISTS; DILTIAZEM; LIVER CIRRHOSIS; RENAL FUNCTION; ATRIAL NATRIURETIC FACTOR; PERFUSED RAT-LIVER; ESSENTIAL-HYPERTENSION; BLOOD-PRESSURE; PLASMA-LEVELS; VERAPAMIL; FAILURE; VASODILATORS; HEMODYNAMICS; PATHOGENESIS